2017
DOI: 10.21276/aimdr.2017.3.5.me13
|View full text |Cite
|
Sign up to set email alerts
|

Awareness and Knowledge on Hypertension and its Self- Care Practices Among Hypertensive Patients in Saudi Arabia

Abstract: Background: Hypertension is a prevalent health problem in Saudi Arabia. It is a major risk factor of morbidity and mortality worldwide. Untreated hypertension can lead to serious and life threatening complications. Prevention of hypertension has a significant role in controlling the disease, which can be achieved by increasing the awareness in the community and changing their attitude and practices towards it. Aim:to assess knowledge, awareness and self-care practicesof hypertension among hypertensive patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

17
23
12

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(55 citation statements)
references
References 16 publications
17
23
12
Order By: Relevance
“…This meta-analysis showed that the pooled estimate of good SCP in Ethiopia stands at 44% (95% CI 34% to 53%). The pooled estimate of good SCP in this study (44%) was lower than that in the study conducted in Saudi Arabia (74.4%) 29 and Ghana (72%) 30 but higher than that in the study conducted in Kenya 13%). 31…”
Section: Discussioncontrasting
confidence: 86%
“…This meta-analysis showed that the pooled estimate of good SCP in Ethiopia stands at 44% (95% CI 34% to 53%). The pooled estimate of good SCP in this study (44%) was lower than that in the study conducted in Saudi Arabia (74.4%) 29 and Ghana (72%) 30 but higher than that in the study conducted in Kenya 13%). 31…”
Section: Discussioncontrasting
confidence: 86%
“…Regarding educational status those Patients who can read and write was 3.7 more likely to practice self-care activities compared to those who are unable to read and write and this finding is similar with study conducted in West Bengal and in Saudi Arabia found that self-management practices were significantly poor among less educated [11,14]. This might be individuals who have better level of education know more about self-care management activities.…”
Section: Factors Associated With Self-care Practice Among Hypertensivsupporting
confidence: 80%
“…Another study in Saudi Arabia showed that awareness, Knowledge and self-management practices were found to be significantly poor among old age groups (above 50 years), males and less educated patients [11].…”
Section: Introductionmentioning
confidence: 99%
“…Regarding educational status those Patients who can read and write was 3.7 more likely to practice self-care activities compared to those who are unable to read and write and this finding is similar with study conducted in West Bengal and in Saudi Arabia found that self-management practices were significantly poor among less educated (11,14). This might be individuals who havebetter level of education know more about self-care management activities.…”
Section: This Figure Is High When Compared To Study Conducted In Durasupporting
confidence: 83%